2013
DOI: 10.1590/s2317-17822013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Achados audiológicos em pacientes submetidos ao transplante renal

Abstract: There were no changes in conventional audiological and high-frequency evaluation, or in the central auditory processing. Professionals involved in the care of kidney transplantation recipients must be better informed about the care, prevention, and early identification of auditory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Further, limited studies have investigated speech perception and auditory processing abilities of individuals with CKD. D' Andrea et al [2013] reported poorer performance among half of the individuals with CKD on staggered spondaic word test [D'Andrea et al, 2013]. Few studies have reported poorer auditory processing and speech perception in noise among individuals with CKD [Kumar et al, 2021;Jain et al, 2022].…”
Section: Introductionmentioning
confidence: 99%
“…Further, limited studies have investigated speech perception and auditory processing abilities of individuals with CKD. D' Andrea et al [2013] reported poorer performance among half of the individuals with CKD on staggered spondaic word test [D'Andrea et al, 2013]. Few studies have reported poorer auditory processing and speech perception in noise among individuals with CKD [Kumar et al, 2021;Jain et al, 2022].…”
Section: Introductionmentioning
confidence: 99%